A Bibliometric Review of ESG Disclosure and Stock Price Crash Risk Studies in the Food and Beverage Industry of Emerging Markets: Evidence from Indonesia - Okta Antika Prasetiya; Siti Mujanah; Achmad Yanu Alif Fianto (International Journal of Economics and Management Research, 2025)
This study conducts a bibliometric analysis of the relationship between Environmental, Social, and Governance (ESG) disclosure and stock price crash risk (SPCR) in Indonesia’s food and beverage industry, focusing on emerging markets. Using a descriptive-quantitative approach, we analyzed 1,000 publications from Crossref (2019–2025) with Publish or Perish and VOSviewer to identify trends, influential authors, and thematic clusters. Results indicate a robust academic focus, with a high citation impact (h-index: 42; 7.11 citations per paper). Keyword co-occurrence and co-citation analysis reveal three major clusters: (1) ESG’s influence on market dynamics, (2) SPCR mitigation strategies, and (3) challenges unique to emerging markets. Network visualizations demonstrate strong linkages between ESG transparency and reduced stock volatility, while temporal overlays show an evolution from crisis-driven studies to sustainability-oriented frameworks. The study contributes original insights as one of the first bibliometric reviews in this niche, highlighting ESG disclosure as a critical tool for risk management in volatile markets. Practical implications suggest that firms and policymakers should adopt standardized ESG reporting to enhance investor confidence and financial stability. Future research should address fragmentation in co-authorship networks and expand sectoral/geographic coverage to strengthen interdisciplinary collaboration between finance, governance, and sustainability scholars.